Lokasi Alternatif TPS 3R (Studi; Kelurahan Purwokerto Kulon, Kabupaten Banyumas) - Chahya Chairani; Dwi Nowo Martono; Sri Wahyono (Postgraduate, University of Mataram, 2023)
Purwokerto is planning to build Tempat Pengolahan Sampah Reduce, Reuse, Recycle (TPS 3R) in each of its villages, this is due to minimize the quantity of waste that will be transported to Tempat Pembuangan Akhir (TPA), 12 TPS 3R have been built in 12 urban villages ini this city. South Purwoketo Subdistrict only has 1 TPS 3R in 1 village while there are 6 village that do not yet have TPS 3R, so the location of this research is in Purwokerto Kulon which is close to the activity center of Purwokerto. This study aims to find an alternative location for TPS 3R in Kelurahan Purwokerto Kulon. The method used in this study uses the AHP method and Spatial Analysis. This study resulted in locations that were â€œVery Appropriateâ€, â€œSufficiently Appropriateâ€ and â€œNot Appropriateâ€. There are 3 alternative location points with the